Parenting Styles in the Film 20th Century Women (2016): An Issue of Generation Gap - Cahyati, Virgi Widya; Gandana, Isti Siti Saleha; Dallyono, Ruswan (Universitas Pendidikan Indonesia, 2024)
Parenting styles can be influenced by a number of sociocultural factors, one of which is generation gap. This study analyses the kinds of parenting styles evident in the film 20th Century Women (2016). The study specifically focuses on the main character Dorothea’s ways of raising her son Jamie, who is forty years apart in age. The analysis points to three different parenting styles adopted by Dorothea: (1) authoritative, (2) authoritarian, and (3) permissive. The study confirms that generation gap has influenced the kinds of parenting styles adopted by the character. This study has thus shed light on an important sociocultural as well as contextual factor influencing parenting style.